WONKA and OOMMPPAA: analysis of protein–ligand interaction data to direct structure‐based drug design. Issue 3 (1st March 2017) - Deane, Charlotte M.; Wall, Ian D.; Green, Darren V. S.; Marsden, Brian D.; Bradley, Anthony R.
Abstract : The background to and development of WONKA and OOMMPPAA, tools for structure‐based drug design, are described. Abstract : In this work, two freely available web‐based interactive computational tools that facilitate the analysis and interpretation of protein–ligand interaction data are described. Firstly, WONKA, which assists in uncovering interesting and unusual features (for example residue motions) within ensembles of protein–ligand structures and enables the facile sharing of observations between scientists. Secondly, OOMMPPAA, which incorporates protein–ligand activity data with protein–ligand structural data using three‐dimensional matched molecular pairs. OOMMPPAA highlights nuanced structure–activity relationships (SAR) and summarizes available protein–ligand activity data in the protein context. In this paper, the background that led to the development of both tools is described. Their implementation is outlined and their utility using in‐house Structural Genomics Consortium (SGC) data sets and openly available data from the PDB and ChEMBL is described. Both tools are freely available to use and download athttp://wonka.sgc.ox.ac.uk/WONKA/ andhttp://oommppaa.sgc.ox.ac.uk/OOMMPPAA/ .